SMOKING, GENDER AND EDUCATION: DISCOURSES, PREVENTION AND EDUCATIONAL PRACTICES IN HEALTH - Valéria Balbino Canuto, Christiane; Elisa de Oliveira Alho, Ana; Nelson Martins Júnior, Leonidas; Resende da Silva, Thiago (Revista Gênero e Interdisciplinaridade, 2026)
This article analyzes educational discourses and practices aimed at preventing smoking among adolescents, with an emphasis on gender relations. Based on a narrative literature review, studies published between 2022 and 2025 that address the interface between health, education, and youth were systematized. The results were organized into two categories: (1) educational strategies in the school and community context and (2) discourses and perceptions about smoking and gender. The analysis showed that educational actions focused on listening, dialogue, and intersectorality have a greater impact on the critical formation of adolescents. Furthermore, preventive campaigns still reproduce moralizing and stigmatizing discourses, especially directed at girls, which can compromise adherence to care practices. It is concluded that smoking prevention requires approaches sensitive to social markers, especially gender, promoting integrated, emancipatory educational practices connected to youth realities.